Intellectual Capital and Innovation: A Necessary Synergy - Ugalde Binda, Nadia (2011)
Many studies have been done to measure the company’s intellectual capital, but few demonstrate its relationship with the creation of competitive advantages that turninto profits. There is a general belief that the survival of companies and their ability to generate profits are closely linked to its ability to reinvent itself. fortunately, innovation does not necessarily come from higher investments in research, its main source is the intellectual capital that improves the products and services and the efficient use of resources. In the present study has collected information on intellectual capital and previousstudies on success factors relating to innovation. Turning intellectual capital into competitive advantage and innovation in earnings should be companies’ the goal.